Numerical investigation of a novel hybrid wind-wave system and its variable pneumatic chamber volume control (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This work presents a numerical investigation of a novel control system for a new hybrid wave-wind energy floating platform. It comprises the design of a control system for controlling the variable pneumatic chamber volumes coupled with the hydrodynamics of the floating platform to maximise wave power production. The numerical model is developed in the object-oriented non-casual language Modelica, for which a new module for the control system was integrated into an existing package developed at IST/ULisboa. A sensitivity analysis of the main control parameters in terms of techno-economic parameters is performed and analysed. Results show that the envelope of control parameters’ values for increasing conversion efficiencies and power production is narrow, and an increase of about 30% was achieved with the best case compared with the base case. Moreover, it was observed that the variable volume of the pneumatic chambers shows significant variations on a part of the operational periods typical of the west of Portugal.